Hydrogen Storage Characteristics of Metal Hydro-Borate and Transition Element-Added Magnesium Hydride - Song, Myoung Youp; Kwak, Young Jun; Park, Hye Ryoung (Korean Journal of Metals and Materials, 2016)
A metal hydro-borate Zn(BH4)2 was prepared by milling ZnCl2 and NaBH4 in a planetary ball mill in an Ar atmosphere. This sample contained NaCl. 95 wt% MgH2-2.5 wt% Zn(BH4)2-2.5 wt% Ni samples [named MgH2-2.5Zn(BH4)2-2.5Ni] were then prepared by milling in a planetary ball mill in a hydrogen atmosphere. The hydrogen absorption and release properties of the prepared samples were investigated. In particular, variations in the initial hydriding and dehydriding rates with temperature were examined. MgH2-2.5Zn(BH4)2-2.5Ni dehydrided at the fourth cycle contained Mg, MgO, and small amounts of -MgH2 and Mg2Ni. The sample after hydriding-dehydriding cycling had a slightly smaller average particle size and a larger BET specific surface area than the sample after milling. Increasing the temperature from 573 K to 623 K led to a decrease in the initial hydriding rate. The initial dehydriding rate increased as the temperature increased from 573 K to 643 K. At 573 K under 12 bar H2, the sample absorbed 3.85 wt% H for 2.5 min, 4.60 wt% H for 5 min, 4.64 wt% H for 10 min, and 4.80 wt% H for 60 min. The MgH2-2.5Zn(BH4)2-2.5Ni had an effective hydrogen storage capacity (the quantity of hydrogen absorbed for 60 min) of near 5 wt% (4.96 wt% at 593 K). KCI Citation Count: 14